Characterization of TiAlBN Nanocomposite Coating deposited via Radio Frequency Magnetron Sputtering using Single Hot-Pressed Target - Mohd Rosli, z.m.rosli; Kwan, Wai Loon; Jariah, Mohamad Juoi; Nafarizal , Nayan; Zainab , Mahamud; Yusliza, Yusuf (Trans Tech Publications, Switzerland, 2013)
TiAlBN coatings have been deposited at varying bias voltage of 0, -60, and -150 V by radio frequency (RF) magnetron sputtering technique. A single hot-pressed Ti-Al-BN target was used for the deposition process. With glancing angle X-ray diffraction analysis (GAXRD), the nanocrystalline (nc-) (Ti,Al)N phase was identified. In addition, the existence of BN and TiB2 amorphous (a-) phase were detected by X-ray photoelectron spectroscopy (XPS) analysis. Thus, the deposited TiAlBN coatings were confirmed as nc-(Ti,Al)N/a-BN/a-TiB2 nanocomposite. On theother hand, it was found that optimum bias voltage used in present study is -60 V where the deposited TiAlBN coating exhibits an excellent adhesion quality. The adhesion quality of the coatings deposited at -60V bias voltage is classified as HF 1 evaluated using the Rockwell-C adhesion test method (developed by the Union of German Engineers).